A comparison of active versus passive methods of responding to rapid diagnostic blood culture results - Elisabeth L. Chandler; Katie L. Wallace; Elizabeth Palavecino; James R. Beardsley; James W. Johnson; Vera Luther; Christopher Ohl; John C. Williamson (Cambridge University Press, 2022)
Abstract Objective: To compare 2 methods of communicating polymerase chain reaction (PCR) blood-culture results: active approach utilizing on-call personnel versus passive approach utilizing notifications in the electronic health record (EHR). Design: Retrospective observational study. Setting: A tertiary-care academic medical center. Patients: Adult patients hospitalized with ≥1 positive blood culture containing a gram-positive organism identified by PCR between October 2014 and January 2018. Methods: The standard protocol for reporting PCR results at baseline included a laboratory technician calling the patient's nurse, who would report the critical result to the medical provider. The active intervention group consisted of an on-call pager system utilizing trained pharmacy residents, whereas the passive intervention group combined standard protocol with real-time in-basket notifications to pharmacists in the EHR. Results: Of 209 patients, 105, 61, and 43 patients were in the control, active, and passive groups, respectively. Median time to optimal therapy was shorter in the active group compared to the passive group and control (23.4 hours vs 42.2 hours vs 45.9 hours, respectively; P = .028). De-escalation occurred 12 hours sooner in the active group. In the contaminant group, empiric antibiotics were discontinued faster in the active group (0 hours) than in the control group and the passive group (17.7 vs 7.2 hours; P = .007). Time to active therapy and days of therapy were similar. Conclusions: A passive, electronic method of reporting PCR results to pharmacists was not as effective in optimizing stewardship metrics as an active, real-time method utilizing pharmacy residents. Further studies are needed to determine the optimal method of communicating time-sensitive information.